A localised soft tissue and bone enlargement in an infant mandible. (20th June 2013) - Sen, Subhalakshmi; Kamath, Abhay; Gupta, Mukund; Radhakrishnan, Raghu
Abstract : A 4-month-old infant was referred by a paediatrician for a rapidly growing swelling on the right side of the mandible of 1.5 months duration. His medical and family history was unremarkable. Palpation divulged a firm and tender enlargement with the overlying soft tissue showing no significant alteration in colour. CT scan revealed cortical irregularity involving the ramus on the right side along with right masseter muscle hypertrophy. Routine haematological investigation yielded values within normal limits except for a raised erythrocyte sedimentation rate. Histopathological examination of the tissue submitted following an open biopsy procedure showed reactive lamellar bone and trabeculae with fibrous marrow exhibiting inflammation. The final diagnosis of infantile cortical hyperostosis was clinched based on the clinicopathological correlation. A rare reactive bone dystrophy which could pose a certain diagnostic dilemma is addressed herewith.